Answer:
The solution of the equation is d=1.
Explanation:
Given : Equation
![-(3d)/(d^2-2d-8)+(3)/(d-4)=-(2)/(d+2)](https://img.qammunity.org/2019/formulas/mathematics/college/6nsu7ztkek50xy3aa6mdlfvnmcae0bkq4e.png)
To find : What is the solution to the equation?
Solution :
Step 1 - Write the equation
![-(3d)/(d^2-2d-8)+(3)/(d-4)=-(2)/(d+2)](https://img.qammunity.org/2019/formulas/mathematics/college/6nsu7ztkek50xy3aa6mdlfvnmcae0bkq4e.png)
Step 2 - Factor the quadratic equation and take RHS to LHS
![-(3d)/((d+2)(d-4))+(3)/(d-4)+(2)/(d+2)=0](https://img.qammunity.org/2019/formulas/mathematics/college/navpxzhc1xp3g43t3769l2yw7b3kystjjd.png)
Step 3 - Take the Least common denominator (LCD)
![(-3d+3(d+2)+2(d-4))/((d+2)(d-4))=0](https://img.qammunity.org/2019/formulas/mathematics/college/4kqqvs4gat4icotu3ctsu76ofi57m2u1sk.png)
Step 4 - Solve the numerator and take denominator to other side
![-3d+3d+6+2d-8=0](https://img.qammunity.org/2019/formulas/mathematics/college/z7kx7mlnr7xib0rgtk4j6j3hxrw7db9jqn.png)
![2d=2](https://img.qammunity.org/2019/formulas/mathematics/college/y4uqoefir3cqic1pg6k4swlrl9e05k92oo.png)
![d=1](https://img.qammunity.org/2019/formulas/mathematics/college/now7vbj5mzzm8nqobe5pmtknuzlpqv3ao6.png)
Therefore, The solution of the equation is d=1.